Effect of process parameters on the photocatalytic degradation of phenol in oilfield produced wastewater using ZnO/Fe2O3 nanocomposites - Al Haiqi, Omer; Nour, A. H.; Bargaa, Rushdi; Ayodele, Bamidele V. (Department of Chemical Engineering, Diponegoro University, 2020)
The upstream processing of crude oil is often associated with the presence of phenolic compounds when not properly treated could result in adverse effects on human health. The objective of the study was to investigate the effect of process parameters on the photocatalytic degradation of phenol. The ZnO/Fe2O3 nanocomposite photocatalyst was prepared by sol-gel method and characterized using various instrument techniques. The characterized ZnO/Fe2O3 nanocomposite displayed suitable physicochemical properties for the photocatalytic reaction. The ZnO/Fe2O3 nanocomposite was employed for the phenol degradation in a cylindrical batch reactor under solar radiation. The photocatalytic runs show that calcination temperature of the ZnO/Fe2O3 nanocomposite, catalyst loading, initial phenol concentration and pH of the wastewater significantly influence the photocatalytic degradation of phenol. After 180 min of solar radiation, the highest phenol degradation of 92.7% was obtained using the ZnO/Fe2O3 photocatalyst calcined at 400 ºC. This study has demonstrated that phenol degradation is significantly influenced by parameters such as calcination temperature of the ZnO/Fe2O3 nanocomposite, catalyst loading, initial phenol concentration and pH of the wastewater resulting in highest phenol degradation using the ZnO/Fe2O3 nanocomposite calcined at 400 ºC, initial phenol concentration of 0.5 mg/L, catalyst loading of 3 mg/L and pH of 3.